Exploring the Scientific Rationality of the Phenomenon of “Different Dosage Forms of the Same Prescription” of Chinese Proprietary Medicine Based on Biopharmaceutical Properties of Powder and Pill of Chuanxiong Chatiao Prescription - Qu, Zhong-huan; Liu, Lin; Zhang, Xiao-fei; Guo, Dong-yan; Zhai, Bing-tao; Zou, Jun-bo; Shi, Ya-jun (Frontiers in Pharmacology, 2022)
Background: The 2020 edition of the Pharmacopoeia of the People's Republic of China has 255 prescriptions with different dosage forms, accounting for 21.09% of total number of the prescriptions. However, the scientific rationality of the phenomenon of " Different Dosage Forms of the Same Prescription " of Chinese medicine has been less explored. Based on the theory of " Components in pills release slowly and take effect in slow-acting manner, while in powders release quickly and take effect in fast-acting way ", we provided in vitro dissolution and in vivo pharmacokinetics of Chuanxiong Chatiao powders and pills to rationalize the phenomenon of " Different Dosage Forms of the Same Prescription " of Chuanxiong Chatiao Prescription. Materials and Methods: We measured in vitro dissolution of four analytes (tetramethylpyrazine, ferulic acid, nodakenin, isoimperatorin) of powders and pills according to paddle method, and the corresponding contents of them by LC-MS/MS. We also provided a pharmacokinetic study of powders and pills. Six domestic rabbits were divided into 2 groups, and gave powders and pills (9.85 g/kg) by surgical administration separately. Blood samples were collected at the set time point after drug administration to measure the plasma concentration. Results: The results of in vitro dissolution experiment showed that the dissolution rate of the four analytes in the powder was greater than that in the pill. However, the solubility of tetramethylpyrazine and isoimperatorin was very low in powder and pill, which may be related to their low solubility properties; The results of the in vivo pharmacokinetic study of powders and pills showed that the Tmax (h) of ferulic acid and nodakenin in powder group was 0.420 and 0.053 times than that of pill group and the t1/2 (h) of ferulic acid, nodakenin, and isoimperatorin of powder was 0.910, 0.262 and 0.661 times than that of pill, respectively. Conclusion: The in vitro dissolution curves and some in vivo pharmacokinetic parameters of four analytes can prove the scientific rationality of the TCM theory that " Components in pills release slowly and take effect in slow-acting manner, while in powders release quickly and take effect in fast-acting way ".